Market Timing and Pecking Order Theory in Latin America - Francisco Javier Vásquez Tejos; Hernan Pape Larre (Revista Finanzas y Política Económica, 2021)
This article aims to determine if the capital structure of Latin American companies in the emerging markets of Brazil, Chile, Mexico, and Peru, are managed according to the market timing theory or the pecking order theory. The analysis was based on a non-probabilistic sample of 170 companies, with annual data, from an unbalanced panel, in the period 2010-2018. Regressions were applied with the fixed and random effects method. The results do not show significant evidence indicating that Latin American companies comply with the pecking order theory. Furthermore, there is also no definitive evidence that companies benefit from low share prices to issue capital or from debt issuance in the face of high stock market prices. There are signs that they follow a blend of several theories, which would indicate their characteristics in the capital structure of Latin American companies.